Fitness-to-Drive Screening Measure©: Patterns and Trends for Canadian Users - Sherrilene Classen (Open Journal of Occupational Therapy, 2016)
Background: The Fitness-to-Drive Screening Measure© (FTDS) is an online screening tool that enables proxy raters (caregivers, family members, and friends) to identify at-risk older adult drivers via 54 driving-related items. This study aimed to identify areas in need of improvement for the FTDS by identifying the patterns and trends of Canadian users and providing recommendations to increase the usage, reach, and potential impact of the FTDS as a health promotion tool.